Comparison of Perinatal, Newborn, and Audiometry Results of COVID-19 Pregnant Women - Mehmet Yilmaz; Şerif Aksin; Deniz Balsak; Fazil Avci; Osman Özdoğru; Bekir Helvacıoğlu; Mahmut Erdemoğlu; Yasemin Aboalhasan; Gülsüm Doğan (International Journal of Clinical Practice)
Objective. There are studies on the perinatal outcomes of COVID-19, but the audiometric effects of the maternal immune system against COVID-19 in the newborn are not clear. In this study, we aimed to investigate the relationship between the perinatal outcomes of COVID-19 positive pregnant women and the audiological outcomes of newborns. Materials and Methods. This retrospective, single-center cohort study was conducted with 65 polymerase chain reaction (PCR) positive pregnant women and newborns and 66 normal pregnant women and newborns who were admitted between January 2020–December 2021. Pregnancy data, perinatal outcomes, and newborn hearing test results of pregnant women and newborns were recorded and compared. Results. A total of 131 patients were enrolled in the study. The number of normal pregnant women was 66 (50.4%) and the number of pregnant women who had COVID-19 disease was 65 (49.6%). In general, gestational week, age, parity, biochemical parameters, duration of hospital stay, week of delivery, fetal weight, and apgar scores were compared between pregnant women with COVID-19 and normal. White blood cell (WBC), neutrophil, aspartate aminotransferase (AST), and C-reactive protein (CRP) parameters were found to be significantly higher, and lymphocyte and neutrophil/lymphocyte (N/L) ratios were significantly lower (p<0.05). There was no statistically significant difference between the two groups (χ2=0.001; p=1,000). The normal delivery status, the normal delivery rate in patients with COVID-19 was found to be statistically significantly higher than the cesarean section delivery status (p=0.012). In the statistical comparison between the COVID-19 and normal pregnant groups in the cesarean section group, the gestational week, delivery week, and apgar1 scores of the pregnant women with COVID-19 were found to be significantly higher. There was no statistically significant difference between the distributions of the rate of infants with hearing impairment in the comparison with hearing tests in pregnant women with COVID-19 (n=1) and normal pregnant women (n=1) (χ2=0.001; p=1,000). Conclusion. Although the negative effects of COVID-19 on pregnancy outcomes are rare, it was determined that there was no increased audiological risk factor, and the most important predictor of COVID-19 was lymphopenia.